Ergonomics in the laboratory environment. - Ala M; Bagot G (Nursing Management, 1994)
The focus of this report is how ergonomics -- the art of making equipment fit the user -- is applied to video display terminal (VDT) use in order to improve productivity. It is recommended that VDT operators be made more comfortable by using ergonomic chairs and tables. The placement of computer screens and keyboards at the workstations should be tailored to the body and its natural motion in order to decrease physical stress.